2017
DOI: 10.3892/ol.2017.7498
|View full text |Cite
|
Sign up to set email alerts
|

Piperlongumine induces apoptosis and autophagy in leukemic cells through targeting the PI3K/Akt/mTOR and p38 signaling pathways

Abstract: Piperlongumine is an alkaloid compound extracted from Piper longum L. It is a chemical substance with various pharmacological effects and medicinal value, including anti-tumor, lipid metabolism regulatory, antiplatelet aggregation and analgesic properties. The present study aimed to understand whether piperlongumine induces the apoptosis and autophagy of leukemic cells, and to identify the mechanism involved. Cell viability and autophagy were detected using MTT, phenazine methyl sulfate and trypan blue exclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
(47 reference statements)
0
17
0
Order By: Relevance
“…Co-treatment with p38 MAPK inhibitor reduced the complexes-induced apoptosis in HCT116 cells, and was also confirmed by quantification of the levels of phosphorylation of p38α (T180/Y182), indicating p38 MAPK-mediated apoptosis. Wang et al (37) reported that piplartine induces apoptosis and autophagy in leukemic cells through targeting the PI3K/Akt/mTOR and p38 signaling pathways. Moreover, a platinum complex with piplartine caused ROS-mediated apoptosis by ERK1/2/p38 pathway in human acute promyelocytic leukemia HL-60 cells (17).…”
Section: Discussionmentioning
confidence: 99%
“…Co-treatment with p38 MAPK inhibitor reduced the complexes-induced apoptosis in HCT116 cells, and was also confirmed by quantification of the levels of phosphorylation of p38α (T180/Y182), indicating p38 MAPK-mediated apoptosis. Wang et al (37) reported that piplartine induces apoptosis and autophagy in leukemic cells through targeting the PI3K/Akt/mTOR and p38 signaling pathways. Moreover, a platinum complex with piplartine caused ROS-mediated apoptosis by ERK1/2/p38 pathway in human acute promyelocytic leukemia HL-60 cells (17).…”
Section: Discussionmentioning
confidence: 99%
“…Drugs that induce ROS production may promote cancer cell death by activating autophagy. PL has been reported to induce autophagy in kidney, prostate and breast cancer (23), and leukemia cells (38). The increase in LC3-II was reversed by the application of NAC prior to PL treatment, suggesting that ROS were involved in autophagy induction.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous signaling pathways can be involved in autophagy induction. Previously, it was reported that PL exhibits anticancer activity by affecting PI3K/AKT, p38/JNK, MEK/Erk and NF-κB signaling pathways in cancer cells (24,38-40). In the present study, only the Erk pathway was analyzed; it was revealed that the Erk pathway was involved in the anticancer activity of PL in HuCCT-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…p38 MAPK activation through phosphorylation (P-p38) is involved in cell differentiation, autophagy, and apoptosis. [37][38][39] NF-kB p65 subunit/RELA is a protein that in humans is encoded by the RELA gene. RELA as part of NF-kB heterodimer complex is retained in cytosol; upon activation, RELA is translocated into the nucleus.…”
Section: Discussionmentioning
confidence: 99%